2017
DOI: 10.14814/phy2.13271
|View full text |Cite
|
Sign up to set email alerts
|

Is the FVB/N mouse strain truly resistant to diet-induced obesity?

Abstract: C57Bl/6J mice are the gold standard animal model of diet‐induced obesity. These animals become obese with higher adiposity, blood fasting glucose, triglycerides, and total cholesterol when fed a high‐fat diet (HFD). Conversely, the FVB/N mouse line is thought to be resistant to diet‐induced obesity, with low or no weight gain and adiposity in response to a HFD. In this study, we investigated whether FVB/N mice are resistant or susceptible to metabolic disorder that is promoted by a HFD. Biometric parameters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 37 publications
5
15
0
2
Order By: Relevance
“…Our data in the FVB control animals are supported by a study by Nascimento‐Sales et al. that report diet‐induced weight gain, steatosis, and insulin‐resistance. Importantly, all significant differences in the physiological, cellular and biochemical responses of the FGF1‐Tek strain were compared to the FVB Control animals.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our data in the FVB control animals are supported by a study by Nascimento‐Sales et al. that report diet‐induced weight gain, steatosis, and insulin‐resistance. Importantly, all significant differences in the physiological, cellular and biochemical responses of the FGF1‐Tek strain were compared to the FVB Control animals.…”
Section: Discussionsupporting
confidence: 86%
“…), we and others (Nascimento‐Sales et al. ) have found that the FVB/N strain does indeed gain visceral adipose and exhibits characteristics of metabolic syndrome when administered a diet high in saturated fats. An FGF1 ELISA on visceral adipose tissue protein extracts from both FVB Control and FGF1‐Tek mice confirmed that FGF1 was elevated in visceral adipose in our model (Fig.…”
Section: Resultssupporting
confidence: 53%
“…Em nossa pesquisa, encontramos uma série de estudos (24) que utilizaram desta metodologia para indução da obesidade (Hvid, Blouin et al, 2013;Sanghez, Razzoli et al, 2013;Oliveira, Santos et al, 2014;Saleh, El-Maraghy et al, 2014;Donner, Elliott et al, 2015;Kulkarni, Jaji et al, 2015;Lai, Chen et al, 2015;Sladek, Stevens et al, 2015;Baldassano, Amato et al, 2016;Ferramosca, Conte et al, 2016;Grasa-Lopez, Miliar-Garcia et al, 2016;Marin, Rosso et al, 2016;Tung, Lin et al, 2016;Ezquer, Bahamonde et al, 2017;Nascimento-Sales, Fredo-Da-Costa et al, 2017;Ojo, Simenson et al, 2017;Oliveira, Chaves et al, 2017;Porras, Nistal et al, 2017;Sadowska, Gebczynski et al, 2017;Sharma, Kim et al, 2017;Xu, Ye et al, 2017;Li, Feng et al, 2018;Tasyurek, Eksi et al, 2018;Watanabe, Kumazaki et al, 2018) (Tabela 1).…”
Section: Dietas Suplementadas Com Gordura Ou Carboidratosunclassified
“…da linhagem C57BL/6J, que possuem maior prédisposição ao ganho de peso pelo consumo excessivo de calorias(Nascimento-Sales, Fredo-Da-Costa et al, 2017). Considerado o modelo animal padrão ouro da obesidade induzida por dieta, esses animais se tornam obesos com maior adiposidade, glicemia de jejum, triglicérides e colesterol total quando alimentados com dieta hiperlipídica (Nascimento-Sales, Fredo-Da-Costa et al,2017).Embora seja um modelo simples de indução da obesidade, as dietas manipuladas com formulações constantes de gordura e carboidratos trazem a desvantagem de não reproduzir bem o hábito de escolha da alimentação da maioria da população humana(Barrett, Mercer et al, 2016;Marin, Rosso et al, 2016; Xu, Ye et al, 2017).…”
unclassified
“…In general, overfeeding rodents results in increased weight gain and body fat accumulation, although this response very much depends on the rodent strain [ 13 , 14 , 15 ]. Thus, high-fat diet feeding leads to increases in animal body weight and body fat percentage, as compared with those of the normal diet-fed counter partners, either in mice [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] or in rats [ 25 , 26 , 27 ] ( Table 1 ).…”
Section: Rsv Effects In Body Weight and Adipose Tissue Weight Undementioning
confidence: 99%